Effects of Piper sarmentosum Roxb. on hypertension and diabetes mellitus: A systematic review and meta-analysis - Othman, Nur Syakirah; Che Roos, Nur Aishah; Aminuddin, Amilia; Murthy, Jaya Kumar; A. Hamid, Adila; Ugusman, Azizah (Frontiers in Pharmacology, 2022)
Hypertension and diabetes mellitus are among the most prevalent diseases affecting people from all walks of life. Medicinal herbs have garnered interest as potential agents for the prevention and treatment of diabetes mellitus and hypertension due to their multiple beneficial effects. Piper sarmentosum Roxb. (PS) is an edible medicinal plant that has been traditionally used in Asia for treating hypertension and diabetes mellitus. This review is aimed to provide comprehensive information from the literature on the effects of PS on hypertension and diabetes mellitus. A computerized database search was performed on Scopus, PubMed and Web of Science databases with the following set of keywords: Piper sarmentosum AND diabetes mellitus OR diabetic OR diabetes OR hyperglyc*emia OR blood glucose OR HbA1c OR glycated h*emoglobin OR h*emoglobin A1c OR hyperten* OR blood pressure. A total of 47 articles were screened and 14 articles published between the years 1998 until 2021 were included for data extraction, comprising of six articles on antihypertensive and eight articles on antidiabetic effects of PS. These studies consist of two in vitro studies and eleven in vivo animal studies. Meta-analysis of three studies on hypertension showed that PS versus no treatment significantly lowered the systolic blood pressure with mean difference (MD) -39.84 mmHg (95% confidence interval (CI) -45.05, -34.62; P < 0.01), diastolic blood pressure with MD -26.68 mmHg (95% CI -31.48, -21.88; P < 0.01), and mean arterial pressure with MD -30.56 mmHg (95% CI -34.49, -26.63; P < 0.01). Most of the studies revealed positive effects of PS against hypertension and diabetes mellitus, suggesting the potential of PS as a natural source of antidiabetic and antihypertensive agents.